The Teumatok Culture in Aceh Singkil - Anisa Ibrahi (Winaya Inspirasi Nusantara Foundation, 2024)
The distinctive fusion of traditional ideas, spirituality, and social practices that continue to influence the region's identity and culture is highlighted by the research on Teumatok culture in Aceh Singkil. The study's conclusions have shed important light on the Teumatok culture's beginnings, values, customs, and social structure. The study has brought attention to how crucial it is to protect and advance Teumatok culture, since it is a vital component of Aceh Singkil's cultural legacy. The study has added to the body of knowledge on traditional beliefs, spiritual activities, and cultural values. It also lays the groundwork for future research on Aceh Singkil's Teumatok culture.